A Test Method for Damage Diagnosis of Suspension Bridge Suspender Cables. (9th June 2015) - An, Yonghui; Spencer, B.F.; Ou, Jinping
Abstract Suspender cables are one of the most vulnerable components of a suspension bridge; therefore, development of effective methods for damage detection is imperative. Many previous damage detection methods require an accurate finite element model, which is often difficult to obtain. This article proposes a model‐free test method for damage diagnosis of suspender cables that avoids this problem. The method includes two procedures: the mean normalized curvature difference procedure and the curvature difference probability procedure. Numerical results for single and multiple damage cases indicate that: (1) both procedures can be effective for damage diagnosis of suspender cables; (2) small damage can be more easily diagnosed in long suspender cables than short ones, for example, 5% stiffness reduction in long suspender cables can be diagnosed; and (3) noise is generally not a problem, because the signal‐to‐noise ratio can be improved by increasing the pulse excitation magnitude for a suspender cable. The proposed test method does not eliminate the need for manual inspection, but changes it from observation to a more quantified method. All of these points increase the potential of the proposed method for practical applications.